Photophysical and biological investigation of phenol substituted rhenium tetrazolato complexes. Issue 41 (13th August 2019) - Akabar, Nurshadrina; Chaturvedi, Vishal; Shillito, Georgina E.; Schwehr, Bradley J.; Gordon, Keith C.; Huff, Gregory S.; Sutton, Joshua J.; Skelton, Brian W.; Sobolev, Alexandre N.; Stagni, Stefano; Nelson, Delia J.; Massi, Massimiliano
Abstract : Rhenium tetrazolato complexes appended to phenol substituents are exploited for cell labelling. Abstract : The synthesis, structural and photophysical characterisation of four tricarbonyl rhenium(i ) complexes bound to 1, 10-phenanthroline and a tetrazolato ancillary ligand are reported. The complexes are differentiated by the nature (hydroxy or methoxy) and position ( meta or para ) of the substituent attached to the phenyl ring in conjugation to the tetrazole ring. The complexes exhibit phosphorescence emission from triplet charge transfer excited states, with the maxima around 600 nm, excited state lifetime decays in the 200–300 ns range, and quantum yield values of 4–6% in degassed acetonitrile solutions. The nature and position of the substituent does not significantly affect the photophysical properties, which remain unchanged even after deprotonation of the hydroxide group on the phenol ring. The interpretation of the photophysical data was further validated by resonance Raman spectroscopy and time-dependent density functional theory calculations. All the complexes are internalised within cells, albeit to variable degrees. As highlighted by a combination of flow cytometry and confocal microscopy, the species display diffuse cytoplasmic localisation except for the complex with the hydroxy functional group at the para position, which reveals lower accumulation in cells and more pronounced punctate staining. Overall, the complexes displayed low levels of cytotoxicity.